The Complexity of Feminization of Garlic Production in the Era of Trade Liberalization in Northern Thailand1 - Yuki M. (2014)
Trade liberalization has become the new driving force behind agrarian change in Thailand. This article describes a transition from simple to more complex forms of feminization of agricultural wage labor in the garlic cultivating villages of northern Thailand as a result of the liberalization of garlic trade in 2003. As cheaper garlic entered the Thai market from China, Thai garlic farmers had to scale down their garlic production, at least temporarily. While the men cultivated other farm crops and/or had the chance to find nonagricultural wage work, women farmers were forced to work as agricultural wage laborers in addition to growing other crops. As a result, the proportion of women taking part in agricultural activities in the region increased, while labor conditions worsened, a phenomenon often linked to the feminization of agricultural labor. At the same time, local women began to be marginalized in the agricultural job market due to the increasing influx of migrant laborers, regarded as lower in status than women in the region, thus adding a new layer of complexity to the feminization of farm labor. © 2012 Asian Institute of Technology.